2007
DOI: 10.1002/jrs.1707
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering as a probe of intermediate phases in glassy networks

Abstract: Bulk glass formation occurs over a very small part of phase space, and 'good' glasses (which form even at low quench rates ∼10 K/sec) select an even smaller part of that accessible phase space. An axiomatic theory provides the physical basis of glass formation, and identifies these sweet spots of glass formation with existence of rigid but stress-free networks for which experimental evidence is rapidly emerging. Recently, theory and experiment have come together to show that these sweet spots of glass formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
(155 reference statements)
5
31
0
Order By: Relevance
“…[12][13][14] For chalcogenide glasses, Raman scattering played a pivotal role in elucidating the molecular structures and identifying domains of intermediate phases. 15 Raman spectra from Na 2 O -CaO-MgO-Al 2 O 3 -SiO 2 system were interpreted in terms of structural alteration as the composition was altered from the binary end members to more complicated glasses. 16 Addition of CaO and MgO to Na 2 O -SiO 2 glasses acted only to increase the disorder of the network slightly.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] For chalcogenide glasses, Raman scattering played a pivotal role in elucidating the molecular structures and identifying domains of intermediate phases. 15 Raman spectra from Na 2 O -CaO-MgO-Al 2 O 3 -SiO 2 system were interpreted in terms of structural alteration as the composition was altered from the binary end members to more complicated glasses. 16 Addition of CaO and MgO to Na 2 O -SiO 2 glasses acted only to increase the disorder of the network slightly.…”
Section: Introductionmentioning
confidence: 99%
“…A strong NdFeB cylinder magnet (10 mm in diameter, 3 mm in thickness, Jiangdong Magnetic Industry of Ningbo Co. Ltd., Ningbo, China) was placed under each slide to separate and concentrate the gold magnetic nanoparticles to a pellet point. The laser irradiation of the pellets produced Raman spectra of RhB and its characteristic peak at 1510 cm −1 was analyzed to build the calibration curve for melamine since the peaks between 1200 and 1400 cm −1 were prone to interference with the glass background of slides [47]. Each recorded Appl.…”
Section: Synthesis Of Fe 3 O 4 /Au Gold Magnetic Nanoparticlesmentioning
confidence: 99%
“…A review of Raman scattering as a probe of the intermediate phases in glassy networks has been given by Boolchand et al 143 Theoretical, as well as experimental results, showed that glass formation occurs over a range of chemical compositions identified as 'intermediate phases'.…”
Section: Glasses Ceramics Disordered Materials Corrosionmentioning
confidence: 99%